Language neuroscience in the operating room: neurosurgical considerations for multilingual brain tumor patients - Sanchez, Sebastian; Tate, Matthew (Frontiers in Oncology, 2025)
Understanding the neural basis of language is critical for neurosurgical procedures involving awake brain mapping. Advances in neuroimaging have helped reshape traditional models of language organization, highlighting dynamic, bilateral cortical-subcortical hodotopical networks that support language processing through a ventral semantic-focused stream, and a dorsal phonological-focused stream. In the operating room, especially during awake craniotomies for glioma resection, this nuanced understanding of human language is key for minimizing deficits and optimizing outcomes, with additional considerations for bi- and multilingual patients. Direct Electrocortical Stimulation (DES) remains the clinical the gold standard for intraoperative mapping, often supplemented with electrocorticography (ECoG) and pre-operative functional magnetic resonance imaging (fMRI). Selecting appropriate language tasks and assessing linguistic proficiency across all languages involved are crucial for tailoring individualized mapping strategies. A detailed linguistic profile, considering factors such as language proficiency, use, and age of acquisition, may help anticipate functional reorganization patterns and surgical planning. This review synthesizes current neuroscientific literature and insights into language and multilingualism, explores the effects of brain pathology on language processing, and outlines clinical best practices for language mapping in multilingual patients undergoing awake neurosurgery.